Representasi Feminisme dalam Cerpen “Perempuan Itu Pernah Cantik” Karya Mashdar Zainal - Pradicta Nurhuda (Program Studi Magister Linguistik Terapan UNJ, 2022)
The issue of feminism can be seen from several stories in literary works, one of which is short stories. This research was conducted with the aim of looking at the forms of injustice experienced by women based on marginalization, subordination, stereotypes, workload, and violence experienced by the main character in the short story